Academic failure in higher education: Socio-cultural analysis from the perspectives of students and teachers in Mexico - Gallur Santorun, santiago (2018)
This research is part of an inter-institutional project interested in analyzing the perceptions of students and teachers about the factors that affect academic failure. In this paper, academic failure is seen, form the sociocultural approach as a complex phenomenon in which different educational actors take place and are related to personal, social, economic and institutional factors. Socio-cultural studies have paid attention to the understanding of educational problems by pointing out as an important mediator the social and cultural context from which students come and the divergences between home/social and academic cultures that are played within the microsocial contexts of the schools and classrooms. Thus, in this work, academic failure is seen as the interplay between personal, social, economic and institutional factors that enable or not the student to integrate into the academic community, build a sense of belonging/commitment to it and perform with success in their university studies.